2019
DOI: 10.1155/2019/4825075
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin Ameliorates Acrylamide-Induced Hyperlipidemic Cardiomyopathy in Male Rats

Abstract: Acrylamide (AA) is a well-known potent carcinogen and neurotoxin that has been recently linked to atherosclerotic pathogenesis. The present study is aimed at investigating the protective effect of silymarin (SIL) as an antioxidant against AA-induced hyperlipidemic cardiomyopathy in male rats. The obtained results showed that animals exposed to AA exhibited a significant increase in the levels of cardiac serum markers, serum total cholesterol, triglycerides, low-density lipoprotein cholesterol, and very-low-den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
(51 reference statements)
2
6
0
Order By: Relevance
“…The significant increase in the body weight gain of silymarin treated groups might be attributes to the stabilization action of silymarin to the hepatocytes membranes, which exerted protection to the hepatocytes and improved liver function. Moreover, the stimulatory action of RNA and protein synthesis shown by silymarin could be subsequently improved growth and increased body weight gain (14). Furthermore, many researchers have suggested the stimulatory action of silymarin by increasing the transcription of ribosomal RNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant increase in the body weight gain of silymarin treated groups might be attributes to the stabilization action of silymarin to the hepatocytes membranes, which exerted protection to the hepatocytes and improved liver function. Moreover, the stimulatory action of RNA and protein synthesis shown by silymarin could be subsequently improved growth and increased body weight gain (14). Furthermore, many researchers have suggested the stimulatory action of silymarin by increasing the transcription of ribosomal RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated ribosomal production and accelerated protein and DNA biosynthesis could be improving the biosynthesis of structural and functional proteins. Moreover, the stimulatory effect of silymarin may offer more transporters and enzymes, which could enhance different body cells functions (14). Decreased body weight gains in EtBr treated female rats might be associated with the increased oxidative stress, since EtBr toxicity leads to cellular antioxidant defense capacity overloading.…”
Section: Discussionmentioning
confidence: 99%
“…This might result from the different behavior and sensitivity of the used model organism toward AA, different doses, and exposition times of AA, and/or due to manipulation of the model organism that already caused stress. However, the remaining common characteristic is the protection of the model organism against AA-induced oxidative stress via substances with antioxidant properties [38][39][40]. Taken together, the presented results showed that AsA pre-treatment significantly reduces ROS levels and promotes SOD and CAT activity to protect cells exposed to AA.…”
Section: Discussionmentioning
confidence: 63%
“…For neutralizing of free radicals adverse effects, the body has protective barriers like antioxidant enzymes (superoxide dismutase (SOD), catalase, glutathione S-transferase, glutathione peroxidase) and proteins like GSH (Zamani et al, 2017). ACR generates free radicals disrupting the antioxidative state leading to oxidative stress (Abdel-Moneim et al, 2019). This was confirmed in the current study by increasing the blood levels of H 2 O 2 , MDA and NO, this increase is a dose and duration dependants (table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in free radicals and peroxide leads to induction of antioxidant system to compensate that increase till the depletion of antioxidants leading to the decrease of antioxidant levels. Blood antioxidant system include nonenzymatic antioxidant as GSH and enzymatic antoxidants as SOD, catalas, GR and GPx (Abdel-Moneim et al, 2019). Vitamin C is considered the most important water-soluble antioxidant in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%